1995
DOI: 10.1289/ehp.95103s7157
|View full text |Cite
|
Sign up to set email alerts
|

Organization versus activation: the role of endocrine-disrupting contaminants (EDCs) during embryonic development in wildlife.

Abstract: Many environmental contaminants disrupt the vertebrate endocrine system. Although they may be no more sensitive to endocrine-disrupting contaminants (EDCs) than other vertebrates, reptiles are good sentinels of exposure to EDCs due to the lability in their sex determination. This is exemplified by a study of alligators at Lake Apopka, Florida, showing that EDCs have altered the balance of reproductive hormones resulting in reproductive dysfunction. Such alterations may be activationally or organizationally ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
145
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(151 citation statements)
references
References 66 publications
6
145
0
Order By: Relevance
“…It has been suggested that the abnormalities observed in these alligators are similar to those reported following embryonic exposure to the potent synthetic estrogen diethylstilbestrol (DES) (4). Prenatal exposure to DES in both humans and experimental animals has been associated with an array of reproductive abnormalities (5,6).…”
mentioning
confidence: 88%
“…It has been suggested that the abnormalities observed in these alligators are similar to those reported following embryonic exposure to the potent synthetic estrogen diethylstilbestrol (DES) (4). Prenatal exposure to DES in both humans and experimental animals has been associated with an array of reproductive abnormalities (5,6).…”
mentioning
confidence: 88%
“…The simulations allow us to assess whether PCBs pose toxicological risks to killer whale populations either during the past or into the future. Adverse effects of PCBs on wildlife, which have been extensively studied, include changes to immune function, neurological development, endocrine endpoints, and/or reproductive health (41)(42)(43)(44)(45)(46). In the absence of thresholds determined specifically for PCB-related health effects in killer whales, we selected the threshold that was established from a long-term captive feeding study designed to measure the effects of POPs (among which the PCBs dominated) on harbor seals (Phoca vitulina).…”
Section: History Of Pcbs In Southern Resident Killer Whalesmentioning
confidence: 99%
“…Developmental abnormalities due to exposure to endocrine-disrupting drugs (e.g., DES) are also well documented (George and Wilson 1994;Mittendorf 1995;Swan and vom Saal 2001). The importance of small changes in the concentration of endocrine-signaling molecules during critical periods in development has been studied extensively in laboratory animals and wildlife (Colborn et al 1993;Fry 1995;Guillette et al 1995;vom Saal 1989;vom Saal et al 1997).…”
Section: Timing Frequency and Duration Of Exposurementioning
confidence: 99%